Oliver! - Moody, Ron.; Wallis, Shani; Reed, Oliver; Reed, Carol; Shepperton Film Studio (Surrey, United Kingdon Columbia Pictures, 1968)
Musical adaptation of Charles Dickens's classic tale of an orphan who runs away from the orphanage and hooks up with a group of boys trained to be pickpockets by an elderly mentor. Oliver Twist is sold to a Dunstable undertaker after asking for more dinner at the orphanage. Escaping to London he is taken in by Fagin to join his gang of child pickpockets. Wrongly accused of a theft he meets a more kindly gentleman who takes him in, to the concern of one of Fagin's old pupils, the violent Bill Sykes. In the middle is Nancy, Sykes' girl whom Oliver has come to trust.
Summary taken from the internet movie database(http://www.imdb.com/title/tt0063385/).
Library has: VDR-1649 (2 VCDs)
Title from disc.
Based on the book by Charles Dickens.
Screenplay, Vernon Harris ; Producer, John Woolf ; Book, music and lyrics, Lionel Bart ; Music arranger and conductor, John Green ; Associate music supervisor, Eric Rodgers ; Choreographer, Onna White ; Production designer, John Box ; Director of photography, Oswald Morris ; Film editor, Ralph Kemplen ; Art director, Terence Marsh.
Ron Moody (Fagin), Shani Wallis (Nancy), Oliver Reed (Bill Sikes), Harry Secombe (Mr. Bumble), Hugh Griffith (The magistrate), Mark Lester (Oliver), Jack Wild (Artful Dodger).
Oliver Twist
Keywords: Crime -- Family -- Drama; Children -- Domestic violence -- Drama; Children -- Child labor -- Drama; Juvenile delinquency -- Drama; England -- History -- Victorian Era -- Drama; London, England -- History -- 19th century -- Drama; Musical films; Historical films; Novel films